The tea girl of Hummingbird Lane [large type] : a novel - See, Lisa (Wheeler Publishing, A part of Gale, Cengage Learning, 2017)
Li-yan and her family align their lives around the seasons and the farming of tea. There is ritual and routine, and it has been ever thus for generations. Then one day a jeep appears at the village gate the first automobile any of them have seen and a stranger arrives. In this remote Yunnan village, the stranger finds the rare tea he has been seeking and a reticent Akha people. In her biggest seller, Snow Flower and the Secret Fan, See introduced the Yao people to her readers. Here she shares the customs of another Chinese ethnic minority, the Akha, whose world will soon change . Li-yan, one of the few educated girls on her mountain, translates for the stranger and is among the first to reject the rules that have shaped her existence. When she has a baby outside of wedlock, rather than stand by tradition, she wraps her daughter in a blanket, with a tea cake hidden in her swaddling, and abandons her in the nearest city.